MAKNA CINTA BAGI WANITA PRIBUMI YANG BERPACARAN DENGAN ETNIK NEGRO - Irrene C Wayong; Nancy Eva Polak (Journal Of Psychology humanlight, 2020)
Perception of love are closely related to human behavior, as well as the connection of students who are currently dating. A person’s feelings tend to developed when prompted by the right stimulus, even though they are come from different culture background. The purpose of this research is to find the true meaning of love between two individuals of different races. This research is a qualitative research, and uses a study case approach method. The data collecting through a process of observation and interviews. The result of this study reveal that race is not a barrier to interpreting love between two individuals.